NARATOLOGI FILM ADA APA DENGAN CINTA? - P.A, Albertus Rusputranto; Primadewi, Nerfita (Institut Seni Indoensia Surakarta, 2022)
The article “Film Narratology Ada Apa Dengan Cinta?” is a scientific publication based on research results entitled “Film Narrative What's Up With Love? from the Perspective of Structural Semiotics”. The narrative structure of the film What's Up With Love? (director: Rudi Soedjarwo, 2002) was investigated using the modified vertical narrative structural analysis method of Roland Barthes's formulation, and an analysis of its derivatives was made. The derivative vertical narrative structural analysis method is used to read the film's narratology Ada Apa Dengan Cinta?